2018
DOI: 10.1186/s12876-018-0809-8
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal hematoma: a new distinctive sign during emergency upper digestive endoscopy for ammonia ingestion

Abstract: BackgroundSubmucosal hematoma has never been associated with caustic injuries. Long-term follow-up of patients who ingested ammonia is not well known and ammonia ingestion is rare.MethodsIn a Single-center observational study, prospective data were collected from 2009 to 2013, in patients over the age of 14 years old referred for ammonia ingestion. The emergency and follow-up endoscopic data and the outcome were reported.ResultsAmmonia ingestion occurred in 43 patients. Submucosal hematoma of the gastric wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…11 Interestingly, a study conducted in Guadeloupe showed that deliberate ammonia ingestion were more common in older (median: 49 years old) females. 12 An Iranian study also revealed similar older population (average age: 35.38±13.72 years); 88.2% ingested acid. 10 In India, 69% of patients deliberately ingested caustic substances, while 28% ingested caustic substances accidentally or attempted murder (3%).…”
Section: Caustic Injuries Presentation and Outcomementioning
confidence: 69%
See 2 more Smart Citations
“…11 Interestingly, a study conducted in Guadeloupe showed that deliberate ammonia ingestion were more common in older (median: 49 years old) females. 12 An Iranian study also revealed similar older population (average age: 35.38±13.72 years); 88.2% ingested acid. 10 In India, 69% of patients deliberately ingested caustic substances, while 28% ingested caustic substances accidentally or attempted murder (3%).…”
Section: Caustic Injuries Presentation and Outcomementioning
confidence: 69%
“…Submucosal hematoma usually yielded better outcomes (89.3% suffered no stenosis nor death) although the difference is not significant (p=0.4). 12 Alkali ingestion presented in more serious condition (44% on grade IIIB, 19% on grade IIA, and 13% on grade IIIB), compared to acid ingestion (38% on grade I and IIA each, with only 24% on grade IIIA). 9 Higher grade of esophageal injury was associated with increased mortality; in one study in Iran, 83.3% of grade III patients died compared to lower grades (p=0.021).…”
Section: Caustic Injuries Presentation and Outcomementioning
confidence: 88%
See 1 more Smart Citation
“…Of these 43 patients, oropharyngeal lesions were present in 30 (69.8%) and associated with attempted suicidal ingestions in 18 of these patients. Such submucosal hematomas should be differentiated from gastric necrosis to preclude confusion with gastric necrosis which might be an indication for surgical intervention (Gelu-Simeon et al 2018). Lu et al (2014) conducted a seven-year retrospective study of 108 adult patients who ingested corrosive substances in an attempt to identify predictive factors for the development of esophageal stricture and gastric outlet obstruction utilizing a modified Zargar endoscopic mucosal injury grading scale.…”
Section: Adult Patientsmentioning
confidence: 99%